(untitled) (Bangladesh Journal of Botany, 2019)
Water harvesting techniques increase the amount of rainfall per unit area, directing the rainwater to the crop area. The rain water is stored in the soil profile with mulch and similar applications and helps the plant to benefit during the arid periods. Water harvesting techniques can be supported with mulching and fertilizing practices in order to crop yield increase. This study was carried out on 20 years old vineyard in farmers’ garden in 2015 - 2016, produced on dry conditions, with economical prescription for Kilis province. Four different doses of leonardite fertilizer were applied in combination with soil bund rainwater harvesting in the experiment. The highest soil moisture was obtained from 370 mm to 7 kg/vineyard leonardite application. The maximum plant water consumption was determined to be 389.5 mm on average from the application of 7 kg/vineyard fertilizer. The minimum plant water consumption was obtained from the control with 310.7 mm. In terms of yield, there was no difference between 5 and 7 kg/vineyard leonardite fertilizer.